Petros Bouras-Vallianatos and Dionysios Stathakopoulos (2024), eds., Drugs in the Medieval Mediterranean. Transmission and Circulation of Pharmacological Knowledge, Cambridge: Cambridge University Press - Poros, Helios (DELTOS, 2025)
This collective volume outlines the history of medieval medicine as a cross-cultural phenomenon in the Mediterranean region. The contributors adopt an interdisciplinary approach, drawing upon archaeological findings in the study, editing, and comparison of texts. The volume highlights the cultural interaction among Byzantine, Jewish, Islamicate, and Latin medical traditions. Situated within diverse contexts, Drugs in the Medieval Mediterranean reveals how pharmacy and medicine intersected with philosophy, magic, cuisine, religion, alchemy, and politics. By focusing equal attention on the linguistic and medical traditions of the texts, the authors trace and analyse the transmission of scientific knowledge and the trade in medicinal substances across the full breadth of the medieval Mediterranean.